Degradation of MCFC Materials in a 81 cm2 Single Cell Operated Under Alternated Fuel Cell/Electrolysis Mode - Frangini, Stefano; Della Pietra, Massimilano; Della Seta, Livia; Paoletti, Claudia; Pedro Pérez-Trujillo, Juan (Frontiers in Energy Research, 2021)
The possibility of producing hydrogen from molten carbonate steam electrolysis using the well-established Molten Carbonate Fuel Cell (MCFC) technology was explored in this work. For this purpose, a 81 cm2 MCFC single cell assembled with conventional cell materials was operated under alternated fuel cell/electrolysis conditions at 650°C in a binary eutectic Li2CO3-K2CO3 electrolyte for about 400 h after an initial period of 650 h in which the cell worked only in the usual MCFC mode. A rapid cell performance loss in terms of cell internal resistance and electrode polarization was observed as soon as the cell started to work in the alternated fuel cell/electrolysis mode. After test completion, a post-mortem analysis was conducted to correlate the electrochemical response with cell materials degradation. Cell materials of the reverse cell were compared against a reference single cell that was assembled with the same materials and operated only in the fuel cell mode under comparable experimental conditions. Post-mortem analysis allowed to identify several serious stability issues of conventional MCFC materials when used in alternated operation modes. Thus, although the electrolyte matrix appeared almost unaffected, a significant amount of dissolved nickel was found in the matrix indicating that electrolysis operations promote an increasing chemical instability of the NiO oxygen electrode. A serious reduction of electrode porosity was also observed in both NiO oxygen and Ni metal fuel electrodes, which could explain the higher polarization resistance of the reversible cell in comparison to the reference MCFC cell. Furthermore, the oxygen current collector made with conventional 316L stainless steel was found to be seriously corroded under the alternated operation modes. Thus, the observed rapid increase in internal resistance in the reverse cell could be caused, at least in part, by an increased contact resistance between the oxygen electrode and the corroding current collector structure. Possible solutions for improving stability of electrodes and of the oxygen current collector in reverse MCFC cells were proposed and discussed in the final part of the work.